Glass solidification block mass
By using agglomerates containing powdered glass and borate inorganic compound binders as glass solidification materials, the problem of instability of glass melt in the prior art is solved, and rapid and stable glass melting and efficient solidification of radioactive wastes are achieved.
Patent Information
- Application Number
- CN202380065581.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-02-03
- Filing Date
- 2023-09-22
- Publication Date
- 2025-04-18
AI Technical Summary
The existing glass solidification materials have instability during the melting process and are difficult to melt quickly, which affects the effective solidification of radioactive waste.
Agglomerates containing powdered glass and a specific adhesive are used as glass solidification materials. The adhesive contains borate inorganic compounds, which improves the melting properties of the glass.
The stable and high-speed melting of the glass is achieved, which shortens the melting time, improves the solidification efficiency of radioactive waste, and inhibits the formation and separation of the yellow phase.
Smart Images

Figure CN119856233A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a glass solidification agglomerate. Background Art
[0002] Radioactive materials and radioactive waste contaminated by radioactive materials are produced in facilities such as nuclear power plants and spent fuel reprocessing plants. This radioactive waste cannot be disposed of in the same way as general waste, so it is generally solidified with cement, glass, etc., sealed in a storage container such as a barrel or a stainless steel canister, and then disposed of in a landfill. Examples of methods for solidifying radioactive waste include the liquid-fed direct current ceramic melting furnace method (LFCM method).
[0003] Technology development related to the solidification of radioactive waste is being widely carried out. For example, Patent Document 1 discloses a technology that can reduce the amount of hydrogen generated by radiation by solidifying radioactive waste using a geopolymer material and a boron compound.
[0004] In addition, Patent Document 2 discloses the following technology: by heating and melting a mixture including a titanium-containing adsorbent that adsorbs radioactive elements, a SiO2 source and an M2O source (M is an alkali metal element) to form a glass solid, the titanium-containing adsorbent that adsorbs radioactive elements can be vitrified, and by sealing the titanium-containing adsorbent that adsorbs a large amount of radioactive elements, the dissolution of radioactive elements can be further suppressed.
[0005] In addition, Patent Document 3 discloses the following technology: by containing iron phosphate glass containing Fe2O3 and P2O5 in a specific composition ratio and the residue of sludge from which the sulfur component has been removed during vitrification, sludge containing sulfate can be vitrified with a high filling effect, thereby providing a glass solid of radioactive waste with excellent chemical durability.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2022-116814
[0009] Patent Document 2: Japanese Patent Application Publication No. 2019-174482
[0010] Patent Document 3: Japanese Patent Application Publication No. 2014-142336 Summary of the invention
[0011] Problems to be solved by the invention
[0012] As disclosed in Patent Documents 1 to 3, solidifying materials for solidifying radioactive waste have been developed for various purposes. As constituent materials of the solidifying materials, cement, glass, etc. are used, and from the viewpoint of easily and stably enclosing radioactive substances for a long time, glass that can be preferably used for solidifying any type of low-level and high-level radioactive waste has attracted attention.
[0013] In the past, as a solidification material (glass solidification material) for solidifying radioactive waste using glass as a constituent material, block glass was used. In this case, solid glass was melted, mixed with radioactive waste, and dissolved, but block glass was not easy to melt, and there was a problem of unstable melting of glass. In devices such as solidification and melting furnaces for radioactive waste, due to the strong radioactivity, remote automatic operation and stable operation without human intervention are required, and it is required to suppress the unstable melting of glass.
[0014] Therefore, the technical problem of the present invention is to provide a briquette for vitrification of radioactive waste that can be easily melted.
[0015] Solutions for solving problems
[0016] The present inventors have conducted intensive studies and have found that the above-mentioned technical problems can be solved by using agglomerates containing powdered glass and a specific binder as a glass solidifying material, thereby completing the present invention.
[0017] That is, the gist of the present invention is as follows.
[0018] [1] A radioactive waste vitrification agglomerate comprising a powdered vitrified material and a binder, wherein the binder comprises a borate inorganic compound.
[0019] [2] The briquettes for vitrification of radioactive waste according to [1], wherein the content of the binder is 0.1% by mass or more and 20% by mass or less.
[0020] [3] The briquette for vitrification of radioactive waste according to [1] or [2], wherein the bulk density is 1.0 g / cm 3 Above and 1.7g / cm 3 the following.
[0021] [4] The briquettes for vitrification of radioactive waste according to [1] or [2], wherein the porosity is 10% or more and 70% or less.
[0022] [5] The agglomerate for vitrification of radioactive waste according to any one of [1] to [4], wherein the average particle size (D50) of the vitrified material is less than 100 μm.
[0023] [6] The agglomerate for vitrification of radioactive waste according to any one of [1] to [5], wherein the cation contained in the borate is at least one cation selected from the group consisting of cations of alkali metals and cations of alkaline earth metals.
[0024] [7] The briquette for vitrification of radioactive waste according to any one of [1] to [6], wherein the briquette for vitrification of radioactive waste is spherical.
[0025] [8] The briquettes for vitrification of radioactive waste according to any one of [1] to [7], wherein the compressive strength under parallel plane load measured by a uniaxial pressure test is 1 N or more.
[0026] [9] Use of the glass solidification agglomerate according to any one of [1] to [8] for glass solidification of radioactive waste.
[0027]
[10] A method for producing a glass solid of radioactive waste, comprising: a melting step of obtaining a mixed melt by mixing a glass solidifying agglomerate as described in any one of [1] to [8] and liquid radioactive waste while heating them, or by heating them after mixing them; and a solidification step of cooling and solidifying the mixed melt to obtain a glass solid.
[0028] Effects of the Invention
[0029] According to the present invention, it is possible to provide a briquette for vitrifying radioactive waste that can be easily melted. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a graph showing the evaluation results of the collapsibility of the glass solidifying material in Experiment 1 of the embodiment (instead of the photograph of the accompanying drawing). DETAILED DESCRIPTION
[0031] Hereinafter, an embodiment of the present invention will be described in detail, but this description is an example (representative example) of the embodiment of the present invention, and the present invention is not limited to this content unless it exceeds the gist of the invention.
[0032] In the present specification, a numerical range expressed by "to" means a range including the numerical values described before and after "to" as the lower limit and the upper limit, and "A to B" means A or more and B or less.
[0033] In addition, in this specification, when it is described as "C or more and D or less", these can be treated as different numerical ranges. In addition, when the lower limit and upper limit of the numerical range are described separately, the numerical range can be set to a range formed by combining any lower limit and any upper limit therein.
[0034] Furthermore, in the present specification, the expression "A or B" may be understood as "at least one selected from the group consisting of A and B".
[0035] In addition, although a plurality of embodiments are described in this specification, various conditions in the respective embodiments can be mutually applied within the applicable range.
[0036] <Composition of the glass solidification agglomerate>
[0037] A glass solidification agglomerate (hereinafter also referred to simply as "glass solidification agglomerate" or "agglomerate") according to one embodiment of the present invention is a glass solidification agglomerate of the following radioactive waste, which contains a powdered vitrified material and a binder, and the binder contains a borate inorganic compound.
[0038] In this specification, agglomerates refer to objects formed by solidifying powdery substances.
[0039] In the past, spherical block glass with a diameter of 1 to 2 mm has been used as a glass solidifying material (hereinafter also referred to as a "solidifying material") for melting and solidifying radioactive waste. When trying to melt such block glass and radioactive waste, the contact surface between the glass and the radioactive waste is small compared to the volume, and the glass and the radioactive waste are not easy to melt, so there is a problem that the time until complete melting becomes long. It should be noted that in order to shorten the melting time by reducing the volume of the glass, it is considered to use powdered glass as a solidifying material. However, when using powdered glass, in the manufacture of the powder, in addition to the manufacture of the solidified body, there will be problems such as powder scattering and clogging of the piping through which the powder passes.
[0040] On the other hand, when the glass solidification agglomerate of the present embodiment is used as a solidification material and the agglomerate is put into radioactive waste, since the radioactive waste contains nitric acid and the like, the dissolution of the binder containing the boric acid inorganic compound into the radioactive waste will be carried out first in the pre-melting process of the powdered vitrified material. Thus, in this case, the collapse of the agglomerate and the penetration of the radioactive waste into the interior of the agglomerate occur rapidly, and a slurry containing radioactive waste, powdered vitrified material and borate inorganic compound is obtained. By becoming this slurry, the contact area between the radioactive waste and the glass increases, so the melting of the glass becomes easier compared with the previous treatment of slowly melting from the surface of the block-shaped glass. The facilitation of the melting of the glass specifically refers to the melting of the glass stably and at a high speed. In addition, a powdered vitrified material with a smaller volume than the block-shaped glass body used in the past is used as the glass to be melted, so the time until all the glass is dissolved can be shortened.
[0041] In addition, in this specification, the term "bulk glass" is used as an expression to indicate glass having a volume larger than that of a powdered vitrified material.
[0042] In addition, radioactive waste contains elements such as molybdenum that are not easily soluble in glass. It is known that these elements that are not easily soluble in glass produce water-soluble compounds such as molybdates during the process of glass solidification. This water-soluble compound is called a yellow phase (YP), and it is required to suppress the yellow phase that is not dissolved in the glass from leaking out from the solidified body.
[0043] When the glass solidification agglomerate of this embodiment is used, the vitrified material is easily melted, thereby promoting the dissolution of radioactive waste components such as molybdic acid into the glass, and the generation and separation of a yellow phase are less likely to occur at the end of melting, thereby suppressing precipitation.
[0044] Generally speaking, radioactive waste is roughly divided into low-level radioactive waste and high-level radioactive waste. In addition, generally speaking, cement and the like are used as constituent materials for solidification of low-level radioactive waste, and glass and the like are used as constituent materials for high-level radioactive waste from the viewpoint of easy long-term stable sealing of radioactive substances. Basically, constituent materials such as glass that can be used for solidification of high-level radioactive waste can also be used for solidification of low-level radioactive waste.
[0045] Therefore, the briquettes of this embodiment are objects obtained by sealing radioactive waste with glass and solidifying it, and therefore can be used for solidifying both low-level radioactive waste and high-level radioactive waste, and are preferably used for solidifying high-level radioactive waste.
[0046] [Powdered vitrified material]
[0047] The powdered vitrified material is not particularly limited as long as it is a vitrified material in a shape generally recognized as a powder.
[0048] Vitrified material is a material that is formed by components constituting glass and becomes a part of glass when melted and solidified. Specifically, the vitrified material can be glass itself, or it can be a substance formed by components constituting glass such as silicon dioxide, silica sand or aluminum oxide, and specifically, glass, silicon dioxide, silica sand, aluminum oxide, boric acid, calcium carbonate, zinc oxide or boron oxide can be listed. These materials can be used alone or in combination of two or more. From the perspectives of raw material cost, improving the ease of vitrification, improving the uniformity of the composition, it is preferred to use at least powdered glass. Thus, as a powdered vitrified material, for example, only powdered glass can be used, and in addition, a mixture of powdered glass and powdered silicon dioxide can also be used.
[0049] It is important that the "powdered vitrified material" is smaller than bulk glass used in the past, and usually has an average particle size (D50) of 500 μm or less.
[0050] The content ratio of the powdered vitrified material in the agglomerate is not particularly limited, and is generally 80% by mass or more and 99.9% by mass or less, preferably 85% by mass or more and 99.9% by mass or less, more preferably 90% by mass or more and 99.9% by mass or less, and further preferably 95% by mass or more and 99.9% by mass or less. If the content ratio is above the lower limit of the above range, sufficient encapsulation of radioactive waste can be ensured. In addition, if the content ratio is below the upper limit of the above range, melting with radioactive waste becomes easy.
[0051] The upper limit of the content ratio may be 99% by mass or less, 98% by mass or less, 97% by mass or less, or 96% by mass or less.
[0052] The average particle size (D50) of the powdered vitrified material is not particularly limited, and is usually 1 μm or more and 500 μm or less, preferably 5 μm or more and 300 μm or less, more preferably 10 μm or more and 250 μm or less, more preferably 10 μm or more and 200 μm or less, further preferably 10 μm or more and 150 μm or less, particularly preferably 10 μm or more and 100 μm or less, and particularly preferably 10 μm or more and less than 100 μm. If the average particle size is below the upper limit of the above range, briquetting becomes easy, and the solubility in radioactive waste is improved. In addition, if the average particle size is above the lower limit of the above range, it is easy to suppress the scattering of the powdered vitrified material during agglomerate manufacturing.
[0053] The average particle size can be measured using a laser diffraction scattering measuring device (for example, Microtrac manufactured by Microtrac BEL Corporation).
[0054] The shape of the powdered vitrified material is not particularly limited, and examples thereof include a particle shape, a short fiber shape (fiber shape or whisker shape), and a scale shape.
[0055] Examples of the powdered glass include crushed glass (obtained by crushing glass) and cut glass (obtained by cutting glass).
[0056] The material type of the powdered glass is not particularly limited, and known glasses can be used, for example, borosilicate glass, soda-lime glass, aluminosilicate glass, aluminoborosilicate glass or phosphate glass. From the viewpoint of easy availability, borosilicate glass, aluminosilicate glass, aluminoborosilicate glass or phosphate glass is preferred, and borosilicate glass is more preferred. In addition, the powdered vitrified material can be a material produced by a known method or a combination of known methods, or a commercially available product can be used.
[0057] The content ratio of the powdered glass in the powdered vitrified material is not particularly limited, and can be 100% by mass, usually 30% by mass or more and 100% by mass or less, preferably 50% by mass or more and 100% by mass or less, more preferably 80% by mass or more and 100% by mass or less, further preferably 90% by mass or more and 100% by mass or less, further preferably 95% by mass or more and 100% by mass or less. If the content ratio is above the lower limit of the above range, it is easy to suppress the raw material cost and vitrification becomes easy.
[0058] Powdered glass can use the glass manufactured by a known method or by combining known methods, and commercially available products can be used. Specifically, commercially available powdered glass can be used, and commercially available glass can be crushed or cut to obtain glass.
[0059] [Adhesive]
[0060] The agglomerate contains a binder for bonding the powdered vitrified material, and the binder contains a borate inorganic compound. The borate inorganic compound has excellent bonding to glass and is easily dissolved in strong acids such as nitric acid, hydrochloric acid or sulfuric acid. Therefore, since radioactive waste contains nitric acid and the like, the inclusion of a borate inorganic compound in the binder can promote the disintegration of the agglomerate in the radioactive waste, promote the formation of a slurry containing radioactive waste and powdered vitrified material, and promote the subsequent melting of the powdered vitrified material.
[0061] The content of the binder in the agglomerate is not particularly limited, and is generally 0.1% by mass or more and 20% by mass or less, preferably 0.3% by mass or more and 15% by mass or less, more preferably 0.5% by mass or more and 10% by mass or less, and further preferably 0.5% by mass or more and 5% by mass or less. If the content is above the lower limit of the above range, sufficient bonding of the powdered vitrified material can be ensured. In addition, if the content is below the upper limit of the above range, the agglomerate is easily disintegrated in the radioactive waste.
[0062] Furthermore, the content ratio of the binder in the above-mentioned agglomerates may also be applied as a preferred content ratio of the borate inorganic compound in the agglomerates.
[0063] There are no particular restrictions on the cations contained in the borate inorganic compound as long as they can form an inorganic compound, and examples thereof include: cations of alkali metals such as lithium (Li), sodium (Na), potassium (K), rubidium (Rb), or cesium (Cs); cations of alkaline earth metals such as beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), or barium (Ba); cations of zinc, etc. These cations may be used alone or in combination of two or more.
[0064] Among these, at least one cation selected from the group consisting of cations of alkali metals and cations of alkaline earth metals is preferred, and Li + 、Na + , K + , Ca 2+ and Sr. 2+ At least one cation in the group consisting of is further preferably selected from Li + and Na + At least one cation in the group consisting of.
[0065] The binder may contain components other than the borate inorganic compound within a range in which the effects of the present invention are obtained.
[0066] The content ratio of the borate inorganic compound in the adhesive is not particularly limited, and is usually 50% by mass or more, preferably 75% by mass or more, more preferably 90% by mass or more, further preferably 95% by mass or more, and particularly preferably 99% by mass or more. If the content ratio is above the lower limit of the above range, it is possible to ensure that the powdered vitrified material is fully bonded. In addition, it is not necessary to set the upper limit of the content ratio, and it can be 100% by mass, or it can be less than 100% by mass, or it can be less than 99% by mass, or it can be less than 95% by mass, or it can be less than 90% by mass.
[0067] The solubility of the binder in water is not particularly limited. From the viewpoint of ease of manufacture and manufacturing stability when water is used as a solvent during agglomerate manufacturing, the saturated solubility in water at room temperature is preferably 0.1 g / 100 mL or more, more preferably 0.5 g / 100 mL or more, and further preferably 1.0 g / 100 mL or more. In addition, the upper limit is not particularly limited, and is usually 10 g / 100 mL or less, and may also be 5 g / 100 mL or less. It should be noted that the solubility of sodium borate is 4.7 g / 100 mL.
[0068] [Other ingredients]
[0069] The agglomerate may contain components other than the powdered vitrified material and the binder (hereinafter also referred to as “other components”) within a range in which the effects of the present invention are obtained.
[0070] The content ratio of other components in the agglomerates is not particularly limited and may be 0% by mass, or greater than 0% by mass, or from 0% by mass to 10% by mass, or from 0% by mass to 5% by mass, or from 0% by mass to 1% by mass.
[0071] The shape of the agglomerate is not particularly limited, and may be, for example, a polygonal prism such as a triangular prism, a quadrangular prism, or a pentagonal prism, a sphere (including a substantially spherical shape), or a flat sphere. From the viewpoint of transportability, a spherical shape is preferred.
[0072] The volume of the agglomerate is not particularly limited, but is usually 0.1 mm 3 Above, can also be 15cm 3 Below, can also be 0.1mm 3 Over and 10cm 3 Below, can also be 0.1mm 3 More than 5cm 3 Below, can also be 1mm 3 More than 5cm 3 Below, can also be 0.1cm 3 More than 5cm 3 Below, can also be 0.3cm 3 More than 3cm 3 Furthermore, for example, when the agglomerate is spherical, the diameter thereof may be 1 mm to 3 cm, 1 mm to 2 cm, or 5 mm to 2 cm.
[0073] If the volume is greater than or equal to the lower limit of the above range, the disintegration property when mixed with the waste liquid is excellent. In addition, if the volume is less than or equal to the upper limit of the above range, the solubility of the powdered vitrified material in the radioactive waste can be improved.
[0074] The bulk density of the agglomerates is not particularly limited, but is usually 1.0 g / cm 3 Above and 1.8g / cm 3 Below, preferably 1.0 g / cm 3 Above and 1.7g / cm 3 Below, more preferably 1.2 g / cm 3 Above and 1.5g / cm 3 Below, more preferably 1.2 g / cm 3 Above and 1.4g / cm 3 If the bulk density is above the lower limit of the above range, sufficient hardness can be ensured. In addition, if the bulk density is below the upper limit of the above range, the solubility of the powdered vitrified material in radioactive waste can be improved.
[0075] The above-mentioned bulk density can be adjusted by adjusting the particle size of the vitrified material and the like.
[0076] The bulk density can be evaluated by a liquid weight method.
[0077] The porosity of the agglomerate is not particularly limited, but is generally 5% to 80%, preferably 10% to 70%, more preferably 20% to 60%, and further preferably 30% to 50%. If the bulk density is above the lower limit of the above range, the infiltration of waste into the agglomerate can be promoted, and the meltability of the powdered vitrified material can be improved. In addition, if the bulk density is below the upper limit of the above range, sufficient hardness can be ensured.
[0078] The porosity can be adjusted by adjusting the particle size of the vitrified material and the like.
[0079] The porosity can be evaluated by comparing the bulk density and the true density, or by mercury intrusion porosimetry.
[0080] The briquette preferably does not deform during the process of transporting or contacting other members, and therefore preferably has a certain degree of hardness. In this specification, the hardness of the briquette is an index of compressive strength based on parallel plane load measured by a uniaxial compression test.
[0081] The compressive strength of the agglomerate measured by the compressive strength test is not particularly limited, and is generally 1N or more, preferably 3N or more, more preferably 5N or more, and further preferably 10N or more. If the compressive strength is above the lower limit of the above range, it is not easy to deform in the process such as transportation. In addition, there is no need to set an upper limit for the compressive strength, but if it is below the upper limit of the above range, sufficient hardness can be ensured. In addition, there is no need to set an upper limit for the compressive strength.
[0082] The compressive strength can be adjusted by the type and amount of the binder.
[0083] The compressive strength can be measured by a uniaxial compressive test under the conditions of a compressive speed of 1 mm / min and a load parallel to a plane.
[0084] <Method for producing agglomerates for glass solidification>
[0085] There is no particular limitation on the method for manufacturing the above-mentioned glass solidification agglomerate. For example, it can be manufactured by a method for manufacturing glass solidification agglomerates which is another embodiment of the present invention (hereinafter also referred to as "method for manufacturing glass solidification agglomerates" or "method for manufacturing agglomerates"). Specifically, it can be manufactured by a method for manufacturing glass solidification agglomerates of radioactive waste which includes the following steps: a mixture preparation step to obtain a mixture comprising powdered vitrified material and a borate inorganic compound; a molding step to mold the mixture to obtain a molded body; and a heat treatment step to heat treat the molded body.
[0086] It should be noted that the method for producing briquettes according to the present embodiment may include steps other than the above-mentioned steps within a range in which the effects of the present invention are obtained.
[0087] [Mixture preparation process]
[0088] The method for producing agglomerates according to the present embodiment includes a mixture preparation step of obtaining a mixture containing a powdery vitrified material and a borate inorganic compound.
[0089] The method for mixing the powdered vitrified material and the borate inorganic compound is not particularly limited, and a known method may be used. For example, the method includes placing the powdered vitrified material and the borate inorganic compound in a container and mixing them using a mixing device such as a ball mill, a pestle or a vibration mixer.
[0090] When using components other than the borate inorganic compound that may be contained in the above-mentioned binder or other components that may be contained in the agglomerate, these components may be mixed together with the powdered vitrified material and the borate inorganic compound during mixing.
[0091] As described above, the powdered vitrified material may be a material produced by a known method or a combination of known methods, or a commercially available product. Specifically, when powdered glass is produced by pulverizing glass, the pulverizing method is not particularly limited, and for example, a jet mill, a bead mill, a ball mill, a hammer mill, a turbo mill, a sand mill, or a freeze pulverizing method may be used.
[0092] As the borate inorganic compound, a compound produced by a known method or a combination of known methods may be used, and a commercially available product may also be used.
[0093] When mixing, a dispersion medium or a solvent may also be used. As a dispersion medium or a solvent, water etc. may be cited, for example. They may be used alone or in combination of two or more. These solvents may be removed from the agglomerate before the agglomerate is finally produced, but may also remain in the agglomerate within the scope of obtaining the effect of the present invention.
[0094] In the mixture preparation step, the constituent materials of the glass solidification agglomerate and the dispersion medium or solvent can be mixed simultaneously. From the viewpoint of ease of manufacture, the constituent materials of the glass solidification agglomerate and the dispersion medium or solvent can be mixed partially and then the rest can be added. For example, the other constituent materials can be added after the binder is dissolved in a solvent such as water.
[0095] [Molding process]
[0096] The method for producing briquettes of the present embodiment includes a molding step of molding the mixture to obtain a molded body. The molding may be performed under pressure or without pressure.
[0097] The method for molding the mixture to obtain a molded body is not particularly limited. For example, the mixture may be molded using a molding die. In this case, a method such as press molding, extrusion molding, or injection molding may be used.
[0098] The molding temperature in the molding step is not particularly limited, and may be, for example, 0° C. or higher and 30° C. or lower.
[0099] The number of moldings is not particularly limited, and may be once, or may be two or more times, preferably two or more times. When the number of moldings is two or more times, specifically, the molding process may at least include the following steps: after molding the mixture to obtain a molded body of a first shape, further molding the molded body of the first shape is performed to obtain a molded body of a second shape.
[0100] [Freezing process]
[0101] The method for manufacturing the agglomerates of the present embodiment may also include a freezing step of freezing the molded body. In the freezing step, the dispersion medium or solvent in the mixture is frozen to improve the adhesion and integrity between the constituent materials of the agglomerates, and the molded body is obtained with a good yield.
[0102] The freezing temperature is not particularly limited, but is preferably equal to or lower than the melting point of the dispersion medium or solvent.
[0103] [Heat treatment process]
[0104] The method for producing briquettes of the present embodiment includes a heat treatment step of heat-treating the molded body. The heat treatment step can be used to dry the molded body, and specifically, the content of water, dispersion medium, solvent, etc. in the molded body can be reduced.
[0105] The method for heat treating the molded body is not particularly limited, and for example, a method of heat treating the molded body using an electric furnace, a gas furnace, or the like can be employed.
[0106] The number of times of heat treatment in the heat treatment step is not particularly limited, and may be once or twice or more.
[0107] The heat treatment temperature in the heat treatment step is not particularly limited, and may be, for example, room temperature or higher and the boiling point of the dispersion medium or solvent or lower.
[0108] <Application of Vitrification Agglomerates in Vitrification of Radioactive Waste>
[0109] Another embodiment of the present invention is the application of the above-mentioned glass solidification agglomerate in the glass solidification of radioactive waste. In this embodiment, the above-mentioned glass solidification agglomerate is used, so compared with the scheme using the previous glass solidification material, the melting of the glass used for glass solidification becomes easy, and efficient solidification can be achieved.
[0110] The method of using the glass solidification agglomerate for glass solidification of radioactive waste can be the same as the method of using a known glass solidification material for glass solidification of radioactive waste. For example, the glass solidification agglomerate is mixed with the radioactive waste while being heated to obtain a mixture of the glass solidification agglomerate and the radioactive waste as the solidification object, as described in the method for producing a glass solidified body of radioactive waste described later.
[0111] The method of mixing the agglomerates for vitrification with radioactive waste is the same as the method described in the method for producing a vitrified body of radioactive waste described later.
[0112] <Method for producing a glass solid of radioactive waste>
[0113] A method for producing a glass solid of radioactive waste according to another embodiment of the present invention (hereinafter also referred to as "a method for producing a glass solid of radioactive waste" or "a method for producing a glass solid") is a method for producing a glass solid of radioactive waste, comprising: a melting step of obtaining a mixed melt by mixing the glass solidification agglomerate and liquid radioactive waste while heating them, or by heating them after mixing them; and a solidification step of cooling and solidifying the mixed melt to obtain a glass solid.
[0114] It should be noted that the method for producing briquettes according to the present embodiment may include steps other than the above-mentioned steps within a range in which the effects of the present invention are obtained.
[0115] [Melting process]
[0116] The method for manufacturing a glass solid body according to the present embodiment includes a melting step, wherein a mixed melt is obtained by mixing the glass solidifying agglomerate and liquid radioactive waste while heating them (hereinafter also referred to as the “first treatment”), or by heating them after mixing them (hereinafter also referred to as the “second treatment”).
[0117] There is no particular limitation on the method of mixing the glass solidification agglomerate and the liquid radioactive waste. For example, there is a method of putting the glass solidification agglomerate and the liquid radioactive waste into a known container such as a melting furnace and mixing them. In the case of the second treatment, there is a method of putting the glass solidification agglomerate and the liquid radioactive waste into a container different from the melting furnace and mixing them. In this case, the mixture obtained here can be put into a container such as a melting furnace and then subjected to the subsequent heating treatment.
[0118] The heating method is not particularly limited, and heating can be performed by a known method.
[0119] The radioactive waste is not particularly limited as long as it contains radioactive substances, and is preferably in liquid form. As described above, the above-mentioned agglomerates for glass solidification can be used for solidification of either low-level radioactive waste or high-level radioactive waste, but the radioactive waste may be either low-level radioactive waste or high-level radioactive waste. From the viewpoint of the high necessity of long-term stable encapsulation of radioactive substances and the viewpoint of the high concentration of nitric acid, it is preferably applied to high-level radioactive waste.
[0120] In the second treatment, the temperature at which the glass solidification agglomerates and liquid radioactive waste are mixed is not particularly limited, but is usually 20° C. to 150° C., or 20° C. to 100° C. When the temperature is within the above range, radioactive waste can be stably treated.
[0121] The heating temperature in the first treatment and the second treatment is not particularly limited, and may generally be 900° C. or higher and 1300° C. or lower. When the temperature is within the above range, the glass solidification agglomerate can be stably melted.
[0122] [Solidification process]
[0123] The method for producing a glass solidified body according to the present embodiment includes a solidification step of cooling and solidifying the mixed melt to obtain a glass solidified body.
[0124] The cooling is preferably performed with the mixed melt sealed in a storage container for storing the final solidified body. Therefore, the method for producing a glass solidified body of the present embodiment preferably includes the following step after the melting step and before the solidification step: accommodating the mixed melt in a storage container such as a stainless steel tank.
[0125] The method for cooling and solidifying the mixed melt is not particularly limited, and a known method may be used. For example, a method of cooling a storage container containing the mixed melt using a coolant, or a method of cooling the storage container and the mixed melt using a cooling gas may be used.
[0126] Example
[0127] The present invention will be described in more detail below with reference to Examples, but the present invention is not limited to the following Examples.
[0128] <Evaluation method of each characteristic>
[0129] [Average particle size of powdered glass (D50)]
[0130] The average particle size (D50) of the powdered glass is measured by a laser diffraction-scattering particle size distribution measurement method.
[0131] [Volume of glass solidification material]
[0132] The volume of the glass solidification material is calculated by weight-density conversion.
[0133] [Collapsibility of glass solidification materials]
[0134] The reagents of stable isotope elements are mixed to produce a simulated solution of radioactive waste. Specifically, the nitrate chemical reagents of each element are dissolved in a 2 mol / L nitric acid aqueous solution so that the concentration of the stable isotope elements in the final solution becomes: 0.26 mol / L for alkali metal elements such as Cs and Rb; 0.06 mol / L for alkaline earth metal elements such as Sr; 0.15 mol / L for transition metal elements such as Cr and Fe; 0.30 mol / L for rare earth metal elements such as La and Ce; 0.10 mol / L for platinum group elements such as Ru; and 0.11 mol / L for other elements such as Zr to produce a simulated solution of radioactive waste.
[0135] Next, under the condition that a load of 30 g was applied to one glass solidifying material using a glass rod, the simulated solution of radioactive waste was put in such a way that half of the glass solidifying material was immersed, and the collapse of the glass solidifying material in the simulated solution of radioactive waste was observed. The time from the time when the simulated solution of radioactive waste was put in until the time when the glass solidifying material began to collapse due to the glass rod with a load of 30 g is shown in Table 1. In addition, regarding Experiment I, the observation results are shown in Table 1. Figure 1 . Figure 1 It is shown that Example 1 began to collapse at the time point of 2.0 minutes, Example 2 began to collapse at the time point of 2.0 minutes, and Comparative Examples 1 and 2 did not collapse even at the time point of 30 minutes. The measurement results of each glass solidification material are shown in Table 1. The expression "-" recorded in Table 1 means that no collapse occurred even at the time point of 30 minutes.
[0136] [Compressive strength of glass solidification materials based on parallel plate load]
[0137] The compressive strength of the glass solidifying material measured by the uniaxial compression test based on parallel plate load was measured by the uniaxial compression test method based on parallel plate load using an autograph at a compression speed of 1 mm / min. The measurement results of each glass solidifying material are shown in Table 1.
[0138] [Bulk density of glass solidification material]
[0139] The bulk density of the glass solidifying material was calculated from the volume and weight obtained from the shape and dimensions. Table 1 shows the measurement results of each glass solidifying material.
[0140] [Porosity of glass solidification material]
[0141] The porosity of the glass solidifying material was calculated from the bulk density and the true density of the powdered glass. The measurement results of each glass solidifying material are shown in Table 1. The true density was obtained by the Archimedean method for bulk glass containing no pores.
[0142] <Experiment I>
[0143] <Manufacturing of glass solidification materials>
[0144] (Example 1-1)
[0145] The glass was pulverized using a ball mill to obtain powdered glass (average particle size (D50): 10.08 μm).
[0146] Next, 40 g of the powdered glass as a raw material glass, 0.3 g of sodium borate as a binder, and 14 g of water were put into a polypropylene container (disposable cup), and mixed using a rotation / revolution mixer (Awatori Rentaro manufactured by THINKY Co., Ltd.) to obtain a mixture.
[0147] Next, fill the mixture to obtain a volume of 0.52 cm 3 The molded body having a spherical shape (radius 0.5 cm) and a hemispherical shape of Teflon (registered trademark) were combined in a mold at a molding temperature of 20° C. and press-molded into a spherical shape.
[0148] Next, the molded body is placed in a refrigerator maintained at -4°C for more than 1 day in a state where the mold is filled in the mold to freeze the solvent, and the molded body formed into a spherical shape is taken out from the mold. Then, in order to remove water, it is kept at 25°C for 24 hours, at 50°C for 1 hour, and further at 85°C for 3 hours in a constant temperature dryer, and returned to room temperature to manufacture a glass solidification material (lump). The content ratio of each component in the glass solidification material is shown in Table 1. It should be noted that the "-" in the component column in Table 1 means that it is not added. This is also the case in Table 2 described later.
[0149] (Example 1-2)
[0150] A glass solidifying material (agglomerate) was produced in the same manner as in Example 1-1 except that the charge amount of sodium borate was changed from 0.3 g to 1.0 g. Table 1 shows the content ratio of each component in the glass solidifying material.
[0151] (Comparative Example 1-1)
[0152] Using the same powdered glass as in Example 1-1 as the raw material glass, 40 g of the powdered glass, 0.4 g of water glass as a binder, and 14 g of water were put into a polypropylene container (disposable cup), and mixed using a rotation / revolution mixer (Awatori Rentaro manufactured by THINKY Co., Ltd.) to obtain a mixture.
[0153] A glass solidifying material was produced by the same method as in Example 1-1 except that the mixture in Example 1 was changed to the above mixture. Table 1 shows the content ratio of each component in the glass solidifying material.
[0154] (Comparative Example 1-2)
[0155] A glass solidifying material (agglomerate) was produced in the same manner as in Comparative Example 1-1 except that the charge amount of water glass was changed from 0.4 g to 1.2 g. Table 1 shows the content ratio of each component in the glass solidifying material.
[0156] [Table 1]
[0157]
[0158] As can be seen from Table 1, in the glass solidifying materials (lumps) of Examples 1-1 and 1-2, which used powdered glass as raw material glass and a substance containing a borate inorganic compound as a binder, they began to disintegrate at 2.0 minutes in the evaluation of disintegrability. On the other hand, in the glass solidifying materials of Comparative Examples 1-1 and 1-2, which used water glass as a binder, no disintegration occurred in the evaluation of disintegrability even after more than 30 minutes.
[0159] <Experiment II>
[0160] <Manufacturing of glass solidification materials>
[0161] (Example 2-1)
[0162] A glass solidifying material (agglomerate) was produced by the same method as that described in Example 1-1. Table 2 shows the content ratio of each component in the glass solidifying material.
[0163] (Example 2-2)
[0164] A glass solidifying material (agglomerate) was produced by the same method as in Example 1-2. Table 2 shows the content ratio of each component in the glass solidifying material.
[0165] (Comparative Example 2-1)
[0166] A glass solidifying material (agglomerate) was produced by the same method as in Comparative Example 1-1. Table 2 shows the content ratio of each component in the glass solidifying material.
[0167] (Example 2-4)
[0168] A glass solidifying material (agglomerate) was produced by the same method as in Comparative Example 2-1. Table 2 shows the content ratio of each component in the glass solidifying material.
[0169] A glass solidification material (lump) was added to a glass sedimentation tube together with a simulated solution of radioactive waste, and the glass solidification material was immersed in the simulated solution. The sedimentation tube was placed in a silicone oil bath maintained at 200° C. for 1 minute. Then, the glass solidification material inside the sedimentation tube was observed using an X-ray CT device, and the evaluation results of the collapse were shown in Table 2.
[0170] The evaluation criteria of collapse are as follows.
[0171] A: The structure of the molded body having a spherical shape or a shape that can be regarded as a part thereof was not observed, and the molded body was collapsed.
[0172] B: A structure having a spherical shape or a shape that can be regarded as a part of the molded body was observed, and the collapse was insufficient.
[0173] [Table 2]
[0174]
[0175] As can be seen from Table 2, when the molded body and the simulated waste liquid were heated and maintained, the molded bodies of Examples 2-1 and 2-2 collapsed within 1 minute, and the molded bodies of Comparative Examples 2-1 and 2-2 did not collapse sufficiently. The present inventors speculate that the reaction between the sodium borate of the binder and the simulated waste liquid was accelerated by heating, so the collapse of the molded body was facilitated.
[0176] Industrial Applicability
[0177] According to the present invention, it is possible to provide a briquette for vitrifying radioactive waste that can be melted more easily than conventional vitrifying materials.
Claims
1. A briquette for vitrification of radioactive waste, wherein: The invention comprises a powdered vitrified material and a binder, wherein the binder comprises a borate inorganic compound.
2. The agglomerate for vitrification of radioactive waste according to claim 1, wherein: The content of the binder is 0.1 mass % or more and 20 mass % or less.
3. The agglomerate for vitrification of radioactive waste according to claim 1 or 2, wherein: Bulk density is 1.0g / cm 3 Above and 1.7g / cm 3 the following.
4. The agglomerate for vitrification of radioactive waste according to claim 1 or 2, wherein: The porosity is 10% or more and 70% or less.
5. The agglomerate for vitrification of radioactive waste according to claim 1 or 2, wherein: The average particle size of the vitrified material, ie, D50, is less than 100 μm.
6. The agglomerate for vitrification of radioactive waste according to claim 1 or 2, wherein: The cation contained in the borate is at least one cation selected from the group consisting of cations of alkali metals and cations of alkaline earth metals.
7. The agglomerate for vitrification of radioactive waste according to claim 1 or 2, wherein: The agglomerates for vitrification of radioactive waste are spherical.
8. The agglomerate for vitrification of radioactive waste according to claim 1 or 2, wherein: The compressive strength under a parallel plane load measured by a uniaxial compression test is 1 N or more.
9. Use of the glass solidification agglomerate according to claim 1 or 2 in the glass solidification of radioactive waste.
10. A method for producing a glass solid of radioactive waste, wherein: include: A melting step, comprising: mixing the glass solidification agglomerate according to claim 1 or 2 and liquid radioactive waste while heating them, or heating them after mixing them, to obtain a mixed melt; as well as In the solidification step, the mixed melt is cooled and solidified to obtain a glass solid.
Citation Information
Patent Citations
Glassification body of radioactive waste and formation method thereof
JP2014142336A
Method for producing radioactive waste solidified body
JP2019174482A
Method for solidifying radioactive waste material and radioactive waste material solidification system
JP2022116814A